Buyer power and the effect of vertical integration on innovation - Claire Chambolle; Morgane Guignard (Deutsches Institut für Wirtschaftsforschung (DIW), 2024)
Our article investigates the impact of vertical integration (without foreclosure) on innovation. We compare cases where either (i) two manufacturers or (ii) a manufacturer and a vertically integrated retailer invest. Then, the independent manufacturer(s) and the retailer bargain over non-linear contracts before selling to consumers. We show that vertical integration always increases the incentives to invest on the integrated product which stifles (resp. spurs) the investment of the independent manufacturer when spillovers are low (resp. high). In contrast, when investments are sequential, if the buyer power is high, the leader independent manufacturer invests more (resp. less) to discourage the integrated retailer's investment when spillovers are low (resp. high). Furthermore, vertical integration is always profitable even when it is not desirable for the industry and welfare. Overall, vertical integration is only desirable for the industry when the buyer power is high and may damage welfare when both the buyer power and spillovers are low.
Keywords: L13; L14; L42; 330; Vertical integration; Investment; Buyer power; Spillovers